Effects of dietary canthaxanthin on egg production, serum parameters, and intestinal health in indigenous chickens under heat stress - Zhou, Xiaoyun; Song, Yiping; Chen, Jie; Chen, Xi; Guan, Lanxin; Wang, Yaxuan; Xiao, Mei; Liu, Wenchao; An, Lilong (Frontiers in Veterinary Science, 2025)
High-temperature environments significantly compromise the productivity of laying hens by damaging intestinal mucosal structure and impairing nutrient absorption. The effects of dietary canthaxanthin (CX) supplementation on egg production rate and intestinal health in Huaixiang chickens raised at high temperatures were assessed in this study. Six groups were randomly selected from among 216 hens: NC (basal diet, 25 ± 1°C), HC (basal diet, 32 ± 1°C for 8 h/day), and four HCX groups (basal diet supplemented with 4, 6, 8, or 10 mg/kg CX, 32 ± 1°C for 8 h/day), with six replicates of six birds each over 28 days. High temperature significantly decreased feed intake, egg production rate, and feed conversion ratio (FCR; p < 0.05), reduced serum total antioxidant capacity (T-AOC), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities (p < 0.05), while increasing malondialdehyde (MDA) and reactive oxygen species (ROS; p < 0.05). High temperature also decreased T-AOC activity in the duodenum, jejunum and ileum (p < 0.05), and increased MDA and ROS levels in these intestinal segments (p < 0.05). Relative to the HC group, dietary CX increased egg production rate and FCR, enhanced serum T-AOC, SOD and GSH-Px activities, while reducing MDA and ROS levels (p < 0.05). CX increased T-AOC activity in the small intestine and decreased MDA and ROS levels (p < 0.05). In addition, heat stress impaired intestinal morphology, lowering villus height (VH), villus surface area (VSA), and villus height to crypt depth ratio (V/C; p < 0.05) while increasing apoptosis rate (p < 0.05). This was accompanied by decreased jejunal fatty acid binding protein 1 (FABP1) expression and lowered serum concentrations of total protein (TP), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C; p < 0.05). Relative to the HC group, dietary CX alleviated intestinal villus atrophy and rupture, effectively maintained normal small intestinal VH, VSA, and V/C ratios, and significantly reduced intestinal epithelial cell apoptosis rate. CX significantly increased serum TP, TG, TC, LDL-C, and HDL-C while maintaining normal expression levels of FABP1 mRNA in the jejunum. These results demonstrate that dietary supplementation with 8 mg/kg CX effectively mitigates high temperature-induced declines in egg production by improving intestinal nutrient absorption.